Variability of residual soil properties - Rahardjo, Harianto (2013)
Rainfall-induced slope failures are commonly observed in residual soil. Due to weathering, the residual soil properties vary with depths, especially in tropical countries, such as: Singapore. Therefore, it is important to characterize the properties of residual soil with depth. Index properties, soil–water characteristic curve and saturated and unsaturated shear strength tests were carried out on residual soils from sedimentary Jurong Formation, Bukit Timah Granite and Old Alluvium in Singapore. The variations of residual soil properties in Singapore were determined from the laboratory test results and evaluated as a function of soil inherent variability. Typical, upper and lower bounds of soil properties for the residual soils in Singapore were described using confidence interval approach and coefficient of variation (COV) in this paper. The variations in residual soil properties can be incorporated in design based on risk or reliability approach. The COV of index and engineering properties of residual soils in Singapore indicate that residual soils from Bukit Timah Granite and Old Alluvium are coarser than residual soil from sedimentary Jurong Formation. The particle size distribution of residual soil from Old Alluvium is more uniform than that from Bukit Timah Granite. On the other hand, the particle size distribution of residual soil from Bukit Timah Granite is more uniform than that from sedimentary Jurong Formation. The shear strengths of residual soils from Bukit Timah Granite and Old Alluvium are higher than that from sedimentary Jurong Formation.